Improving the uptake of cervical screening in pregnant and recently postnatal women: a quality improvement project. Issue 2 (25th May 2022) - Coleridge, Sarah Louise; Wiggans, Alison; Nelissen, Ellen; Bethune, Rob; Blackwell, Richard; Bryant, Andrew; Morrison, Jo
Abstract : Background: In 2018, cervical screening uptake was at its lowest level since screening began, particularly in those aged 25–35, coinciding with the peak incidence of cervical cancer and average age at first delivery. Problem: Retrospective baseline data of pregnant women found 47.3% (n=123/260) were overdue for screening by delivery, of whom 74% (n=91/123) remained overdue by 6 months postnatal. Methods: We undertook a quality improvement project from April 2018 to April 2019 to improve cervical screening uptake in pregnant and postnatal women. We mapped out the screening process and canvassed stakeholders. The main theme was inconsistency of advice received by women. From February 2018 to May 2020, we undertook a prospective audit of 10 women per week who gave birth in our maternity department, recording screening status at delivery and 6 months postnatal. Interventions included introducing evidence-based guidelines about cervical screening in pregnancy and the postnatal period, flow charts for maternity staff, multiprofessional teaching for all maternity staff and information dissemination to women (via the HANDiApp platform, a social media campaign and adapting results letters following colposcopy, highlighting dates when screening would be due). Primary care opening hours were extended for screening and women received a letter from their midwives, if they required cervical screening in pregnancy. Results: Locally, the percentage of women overdue for cervical screening by 6 months postnatal improved by 8.0% during this project, compared with a 1.6% change in national screening rates in women aged 25–49. Conclusions: We increased the percentage of local pregnant and postnatal women attending cervical screening by introduction of a package of information, targeted education and widening access to screening appointments.